DENTINAL HYPERSENSITIVITY: A REVIEW ON EFFECTIVE TREATMENT WITH POTASSIUM NITRATE CONTAINING DENTIFRICE - NIKHIL OJHA (International Journal of Pharma and Bio Sciences, 2013)
Dentinal hypersensitivity is a very common dental disease worldwide, which can cause various problems to patients. The management of this condition requires a good understanding of the complexity of the problem, as well as the variety of treatments available. Various agents are commonly employed like calcium salts, fluorides, ferrous oxide, and strontium chloride etc. This review considers the treatment of dentinal hypersensitivity using the dentifrices containing the nerve desensitizing agent Potassium Nitrate.